The Exercise Vibration Wave Principle in Physical Rehabilitation of Children with Musculoskeletal System Disorders - Nikolaevich Efimenko, Nikolai (2021)
The article describes the methodical and methodological possibilities of the vibration-wave principle of physical exercises in the context of its use in the physical rehabilitation of children with musculoskeletal disorders both in the conditions of the hall for movement therapy and in the aquatic environment using the example of hydrokinesis therapy. The analysis of the well-known healing properties of vibration on the human body, which can be used in the physical rehabilitation of children with musculoskeletal system disorders, is given. The known possibilities of acoustic wave effects on the musculo-fascial and skeletal systems of people are analyzed. The unique possibilities of applying the phenomena of vibration and waves not only on land but also in an aquatic environment, in conditions of hydrokinesis therapy in a pool are considered. The properties of a longitudinal elastic (acoustic) wave and its effect on the musculoskeletal system of children are characterized. The authors proposed a new concept in physical rehabilitation - "correctional acoustic internal field" on land and "correctional hydroacoustic external field" (in water). The methodological aspects of the varieties of using these fields in an autoactive (independent, conscious) version and in an imperative (forced, directing from the outside) version are considered.